A percepção dos estudantes cotistas sobre os fatores que influenciam o desempenho acadêmico: o caso do curso de graduação em Ciências Biológicas da Ufu – campus Umuarama - Duarte, Leandro Dayrell (2021)
The Quota Law in Brazil has been of great importance for entry of Brazilians (who meet the requirements) to the Public University, proving to be necessary to guarantee them the right to education. The objective of the study was to analyze the perception of quota students on the factors that influence the academic performance of quota students in the Undergraduate Course in Biological Sciences - Campus Umuarama - at UFU after the implementation of the Quota Law. The study methodology was documentary research (secondary data) and field research carried out with Quota-holders and Widely Competitiveness students, corresponding to a questionnaire applied to 39 quota- and non-quota students (low and high-performance) of the Biological Sciences course, prioritizing evaluation the factors that influence academic performance. The analysis of secondary data was carried out using a quantitative method in order to assess the academic performance of students from different types of admission. For the field research, qualitative analysis was used with semi-structured interviews whose data were categorized and tabulated for interpretation. The results showed that among the types of entrances, the ones with the highest average (72) of performance was modality 4 (shareholders from Public School/independent of income. The study revealed that among the quotaholders, the motivation to study and dedication were determinant factors for their good performance. The research carried out indicates that there were no significant differences in income between quota holders and non-quota students from the point of view of socioeconomic factors, contrary to studies that place these as indicative of a drop in the university's academic standard. As a technological product, an executive summary was constructed to be presented to the course, containing the findings and some possible actions.